Essential Knowledge Kemasan Bubuk Kopi KSU Buah Ketakasi Kecamatan Silo Kabupaten Jember - Rachmat Udhi Prabowo; Dyah Ayu Nugraheni; Djoko Soejono; Ariq Dewi M.; Julian Adam R. (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
The power of packaging design greatly influences purchasing decisions because unique packaging designs appeal to consumers. In general, the purpose of this activity is to provide training on the importance of coffee product packaging for the sustainability of the Ketatasi Fruit KSU business unit so that it can compete with similar products produced by different companies, with specific objectives: (1) To increase the management's understanding of Ketatasi Fruit KSU's role in packaging in the KSU Ketatasi Fruit ground coffee business; (2) To increase the knowledge of KSU Buah Kettasi managers about the functions, types, and uses of KSU Ketatasi ground coffee product packaging; and (3) To introduce tips on choosing packaging for ground coffee products at KSU Buah Ketaka. Results of the activities (1) The purpose of packaging is to maintain the aroma and taste of ground coffee both when distributed to consumers and when sold in shops, both in traditional markets and supermarkets. Same as long as the user is holding it. If the coffee is not packaged properly, the freshness, smell, and taste of the ground coffee will suffer after a week or two. The durability of ground coffee during packaging is influenced by several factors, namely storage conditions (ambient temperature), degree of roasting, ground coffee moisture content, fineness of the powder, and oxygen content of the packaging. (2) Good packaging materials should have the following characteristics: low water vapor permeability, low oxygen permeability, low aroma and odor permeability, carbon dioxide gas permeability, good oil resistance, etc., good scratch and tear resistance, and be easy and cheap to get.